Sistema de cubicacion para el genero Pinus en la UCODEFO No. 7 "Norogachi-Guachochi", Chihuaha - Pompa Garcia, M.=700 1 Velazquez Martinez, A.; Ramirez Maldonado, H.; Rodriguez Franco, C.; Serrano Galvez, E.
(Es, En)
Ilus., 32 ref.
Keywords: PINUS; CUBICACION DE ARBOLES; TABLAS DE CUBICACION; DENDROMETRIA; MEXICO